In Vitro Study of Picloxidine 0.05 % Antiviral Activity (on the Example of Adenovirus) - G. M. Chernakova; D. Yu. Maychuk; E. A. Klescheva; M. V. Mezentseva; L. I. Russu; I. A. Suetina; E. I. Isaeva (Oftalʹmologiâ)
Introduction. Lack of antiviral drug forms in ophthalmology stimulates to study the efficacy of drugs of other pharmacological groups with potential antiviral activity. Adenoviral eye infections are widespread and highly contagious. Material and methods. The antiviral effect of the drug was estimated by changing the DNA titer of the virus in adenovirus-infected cells, controlling. the specificity of the viral affection by setting PCR in real time. The cytotoxic effect of Vitabact® was studied on Vero cell culture. Results. Installations of the preparation according to the treatment scheme (after infection of the culture) resulted in 2.7-fold decrease in the viral DNA amount. When Vitabact® was injected into cells in dilution of 1/128 (the first dilution of the drug that does not refuse the cytotoxic effect on Vero cells) according to the prophylactic scheme  the level of adenovirus replication decreased by 1.7 times. Conclusions. The preparation of pycloxidine had the maximum antiviral effect in the treatment scheme mode. This circumstance opens the perspective of specifying the spectrum and mechanisms of antiviral effect of pixloxidine and makes it possible to use Vitabakt as a component of the second stage (starting from 10–12 day of the disease) of empirical therapy of viral conjunctivitis.